Gurkha’s Quest for Justice: Possible Remedies for Gurkhas Under International Human Rights System - Sangroula, Geeta Pathak (Kathmandu School of Law Review, 2019)
There is a 205-year long history of Gurkha’s entanglement with the British. In 1816, the British East India Company defeated Nepal in the Anglo-Nepalese war. Dominant narratives of this history suggests that the British were impressed by the war-fighting capabilities and loyalty of the Gurkhas, and recruited them- not as mercenaries but part of their army- to fight in the World Wars, to maintain imperial administration in British India, Burma, Malaya, Singapore, and Hong Kong. After the 1947 Tripartite Agreement between India, Nepal, and Britain, Gurkha soldiers were recruited annually in both British and Indian armies. For decades, the Gurkhas have carried out a movement seeking equal pay and pension in comparison to their British counterpart. After a long struggle, their movement reached the European Court of Human Rights wherein the Court did not find a violation of the European Convention regarding the differential treatment of Gurkha soldiers. The paper, briefly subscribes to the available literatures about the magnitude of problems and the status of Nepali Gurkhas in the British Army, including an overview of the commitments and obligation of United Kingdom towards human rights. The paper fills the scholarly gap by taking international human rights as an analytical framework in approaching the Gurkhas’ issue. In making a case for possible remedies, Gurkhas as ‘rights-holders’ is proposed as a suitable frame. It concludes with recommendations, grounded in international human rights law, as a possible remedial mechanism for the Gurkhas— in their quest of justice. "We never got equal terms and pay, and we are not even bothered about that. What we are seeking is justice for our pensions, getting equal to what the British get, according to the service rendered." (Retired major Tikendra Dal Dewan)